2011
DOI: 10.1097/aap.0b013e3182176f70
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity of Adjuvants Used in Perineural Anesthesia and Analgesia in Comparison With Ropivacaine

Abstract: Background and Objectives Clonidine, buprenorphine, dexamethasone, and midazolam (C,B,D,M) have been used to prolong perineural local anesthesia in the absence of data on the influence of these adjuvants on local anesthetic (LA)-induced neurotoxicity. Therefore, the impact of these adjuvants on ropivacaine (R)-induced death of isolated sensory neurons was assessed. Methods The trypan blue exclusion assay was used to assess death of sensory neurons isolated from adult male Sprague-Dawley rats. Drugs were appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
155
1
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(175 citation statements)
references
References 20 publications
6
155
1
8
Order By: Relevance
“…Although caution is warranted, animal studies have provided encouraging results, concluding that neurological injury is absent [7,14,57]. During in-vitro studies, Ma et al demonstrated a potential protective effect of dexamethasone against local anaesthetic-induced cell injury [58] and a series of 2000 intrathecal injections of 8 mg dexamethasone for the treatment of post-traumatic visual disturbance in 200 patients failed to demonstrate any neurological sequelae [59].…”
Section: Discussionmentioning
confidence: 99%
“…Although caution is warranted, animal studies have provided encouraging results, concluding that neurological injury is absent [7,14,57]. During in-vitro studies, Ma et al demonstrated a potential protective effect of dexamethasone against local anaesthetic-induced cell injury [58] and a series of 2000 intrathecal injections of 8 mg dexamethasone for the treatment of post-traumatic visual disturbance in 200 patients failed to demonstrate any neurological sequelae [59].…”
Section: Discussionmentioning
confidence: 99%
“… Por un lado, su efecto vasoconstrictor podría influir en el retraso de la absorción y eliminación del AL a nivel PN aumentando así la vida media de los AL y su poder de acción 35 .…”
Section: Efecto Analgésico De La Dexametasona Aplicada a Nivel Perineunclassified
“…Sin embargo, existen estudios en animales que sugieren una cierta toxicidad de la dexametasona, concretamente Williams et al 35 en un estudio realizado en ratas, observaron mayor toxicidad e hiperalgesia, cuando la concentración de la dexametasona aumentaba de 66 a 133 µg/ml y era utilizada conjuntamente con ropivacaína. La dosis utilizada en nuestro estudio ha sido de 400 µg/ml, que haciendo un cálculo en proporción al peso medio de cada especie, resultaría en una dosis muy inferior (1.71 µg/ml) a la registrada como peligrosa en el estudio de Williams.…”
Section: Efecto Analgésico De La Dexametasona Aplicada a Nivel Perineunclassified
See 1 more Smart Citation
“…Kako bi se obezbedio što duži analgetski efekat, primenjivan je ili veći volumen ili koncentracija lokalnog anestetika, čime se povećava mogućnost za nastanak neželjnog motornog bloka ili toksičnog efekta lokalnog anestetika. Zbog toga se danas teži ka dodavanju lekova, ili sistemski ili perineuralno, kao i plasiranju katetera i kontinuiranoj administraciji lokalnog anestetika 67 . Tako je pokazan produžen efekat bloka perineuralnom primenom buprenorfina, klonidina, deksametazona, deksmedetomidina illi magnezijuma 68 , ali je i njihova sistemska primena kao rezultat imala gotovo identičan efekat na dužinu trajanja bloka, smanjujući rizik za nastanak oštećenja nerva 69 .…”
Section: Diskusijaunclassified